Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Mediasi pada Karyawan PT Raja Utama Realti - Fityah Karimah Farhah; Yuni Kasmawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of transformational leadership style and work environment on turnover intention, with job satisfaction as a mediating variable among employees of PT Raja Utama Realti. The research employed a quantitative descriptive method with a saturated sampling technique involving the entire population of 60 employees. Data were collected through questionnaires using a Likert scale and processed with Microsoft Excel 2019 and SmartPLS version 4.1.0.9. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results revealed that transformational leadership style had a negative and insignificant effect on turnover intention, while the work environment had a positive and significant effect on turnover intention. Furthermore, job satisfaction showed a negative and significant influence on turnover intention. The findings also indicate that job satisfaction is capable of mediating the influence of transformational leadership style and work environment on turnover intention, highlighting the important role of job satisfaction in reducing employees’ intention to leave the organization.